Usefulness of Perfusion CT to Assess Response to Neoadjuvant Combined Chemoradiotherapy in Patients with Locally Advanced Rectal Cancer - Curvo-Semedo, L (2011)
RATIONALE AND OBJECTIVES: To prospectively evaluate perfusion computed tomography (CT) for assessment of changes in tumor vascularity after chemoradiation therapy (CRT) in locally advanced rectal cancer and to analyze the correlation between baseline perfusion parameters and tumor response. MATERIALS AND METHODS: Twenty patients with rectal cancer underwent baseline perfusion CT before CRT, and in 11 an examination after CRT was also performed. For each tumor, blood flow (BF), blood volume (BV), mean transit time (MTT), and permeability-surface area product (PS) were quantified. The Mann-Whitney U test compared baseline perfusion parameters of responders and nonresponders and pre- and post-CRT measurements were compared by the Wilcoxon signed-rank test (P < .05 statistically significant for both tests). RESULTS: Baseline BF was significantly lower (P = .013) and MTT was significantly higher (P = .006) in responders. Both were able to discriminate responders from nonresponders with a sensitivity of 80% and 100% and a specificity of 73.3% and 86.7%, respectively, for BF and MTT. Baseline BV and PS were not significantly different in responders and nonresponders. Perfusion parameters changed significantly in post-CRT scans compared to baseline: BF (P = .003), BV (P = .003), and PS (P = .008) decreased, whereas MTT increased (P = .006). CONCLUSION: Baseline BF and MTT can discriminate patients with a favorable response from those that fail to respond to CRT, potentially selecting high-risk patients with resistant tumors that may benefit from an aggressive preoperative treatment approach.